Quadruple Primary Malignancies over 2 Years with Germline Mutation in Krebs Cycle Enzyme Gene Fumarate Hydratase - Solaleh Aminian; Fawaz Al-Alloosh; Fatemeh Yadegari; Shiva Zarinfam; Haider Hamza Al-Abedi; Keivan Majidzadeh-A. (Case Reports in Genetics)
Multiple primary cancers (MPCs) are defined as the presence of more than one cancer in an individual that is not due to recurrence, metastasis, or local spread. Different factors such as copathogenic genetic mutations, environmental factors, lifestyle, and first cancer treatment increase the possible occurrence of subsequent malignancies. In recent years, the risk of MPCs has increased due to improved treatment; however, quadruple primary malignancies are still rare and require further investigation and treatment of the underlying cause. Here, we present a 64-year-old man with a 40-year history of cigarette smoking who developed quadruple primary malignancies of the epiglottis, kidney, pancreas, and lung. To investigate the possible genetic cause, we performed WES, and a variant of c.580G > A (Ala194Thr) was discovered in exon 5 of the Krebs cycle enzyme gene, fumarate hydratase (FH). This substitution was classified as VUS in Clinvar and likely pathogenic by Varsome and Franklin software. The structural analysis showed that the variation found was localized in a highly conserved alpha helix in the D2 domain near the FH hinge region (<6 Å), suggesting that enzyme activity was affected by a perturbation in protein quaternary structure. Because of the well-established role of FH mutations in renal cancer risk, it was possible that the FH mutation could have led to the development of renal cell carcinoma in this case. The biological mechanisms of MPCs suggest that subsequent primary malignancies are triggered by the combined effects of environmental factors, such as smoking and genetics.